Keep it positive: Exploring the relationship between stress, positive affect, wellbeing, and success of entrepreneurs - Drnovšek, Mateja; Slavec Gomezel, Alenka (Frontiers in Psychology, 2022)
Entrepreneurs’ well-being is of unprecedented importance given their crucial role in national economies in terms of job creation and innovation. In this research, we used a mixed methods approach to investigate the direct and indirect mechanisms by which entrepreneurs’ well-being mediates the effects of stress on perceived entrepreneurial success. We theorize that entrepreneurs experience work-related stress and that the level of perceived well-being mediates the relationship between the entrepreneurs’ stress and perceived success. We also hypothesize moderation effects by dispositional positive affect. We find that stress has direct negative effects on entrepreneurs’ well-being and perceived success. However, an experience of positive affect significantly weakens the negative effects of stress by broadening and building entrepreneurs’ cognitions. Drawing from our theoretical and empirical findings, we discuss implications for theory and practice in the domain of entrepreneurs’ well-being.